Strategy Of Online Marketing For Products By Autism Café Project Malaysia - Ahidin, Udin; Kasmad, Kasmad; Arianto, Nurmin (Jurnal Pengabdian kepada Masyarakat : Kreasi Mahasiswa Manajemen, 2024)
Marketing online has become an important aspect in any business, including the food industry. With the risee-commerce and social media, food companies must develop marketing strategies online strong to remain competitive in the market. The problem formulation How do employees understand efforts, How to market processed food products ffectively. This Community Service was held by proposing material "Strategy Of Online Marketing For Products By Autism Café Project Malaysia”. After this activity was completed, the PKM organizing team processed the questionnaire data distributed to participants as an evaluation of this activity. In carrying out this PKM activity, Lecture/Presentation, Question and answer method, Sharing Session In increasing sales using online marketing, Marketing strategyOnline, social media used. From the results of PKM regarding understanding with the theme "Strategy Of Online Marketing For Products By Autism Café Project Malaysia” is concluded as follows: The participants presented Comprehensive depth of knowledge and knowledge related to the use of technology in marketing processed products produced byAutism Café Project Malaysia Participantsget into related knowledge about how to market processed products fromAutism Café Project Malaysia effectively and efficiently with a number of that was carried out.